Clinical and genetic analysis in a Chinese cohort of children and adolescents with diabetes/persistent hyperglycemia. Issue 1 (23rd July 2020) - Ding, Yu; Li, Niu; Lou, Dan; Zhang, Qianwen; Chang, Guoying; Li, Juan; Li, Xin; Li, Qun; Huang, Xiaodong; Wang, Jian; Jiang, Fan; Wang, Xiumin
Abstract: Aims/Introduction: To investigate the genetic etiology and evaluate the diagnostic application of next‐generation sequencing for diabetes/persistent hyperglycemia in children and adolescents. Materials and Methods: Patients with diabetes/persistent hyperglycemia, presenting with at least one other clinical manifestation (other than diabetes) or with a family history of diabetes, were recruited. The clinical and laboratory characteristics of the patients were recorded. Next‐generation sequencing was carried out, and candidate variants were verified by Sanger sequencing. Variant pathogenicity was further evaluated according to the American College of Medical Genetics and Genomics guidelines. Results: This study included 101 potential probands, 36 of whom were identified as positive by genetic testing. A further 51.2 and 20.9% of variants were determined to be pathogenic or likely pathogenic, respectively. Variants associated with the disease were primarily identified in 21 genes and three regions of copy number variants. Among the 39 variants in 21 genes, 61.5% (24/39) were novel. The genetic diagnosis of 23 patients was confirmed based on genetic evidence and associated clinical manifestations. We reported GCK variants (21.7%, 5/23) as the most common etiology in our cohort. Different clinical manifestations were observed in one family with WFS1 variants. Conclusions: Our findings support the use of next‐generation sequencing as a standard method in patients with diabetes/persistent hyperglycemia and provide insights into the etiologies of these conditions. Abstract : Few studies have focused on examining the genetic etiology of diabetes in Chinese children and adolescents. A total of 101 potential probands were included in this study to investigate the clinical and genetic features of monogenic diabetes and genetic syndromes associated with it, and evaluate the diagnostic use of next‐generation sequencing for diabetes/persistent hyperglycemia. Our findings expand the gene mutation spectrum and phenotypic spectrum of the rare monogenic diabetes and genetic syndromes associated with diabetes, and provide insights into the current understanding of the underlying etiologies of diabetes/persistent hyperglycemia and support the use of next‐generation sequencing as a diagnostic method in Chinese patients with diabetes/persistent hyperglycemia.